Aging alters the dampening of pulsatile blood flow in cerebral arteries. Issue 9 (September 2016) - Zarrinkoob, Laleh; Ambarki, Khalid; Wåhlin, Anders; Birgander, Richard; Carlberg, Bo; Eklund, Anders; Malm, Jan
Excessive pulsatile flow caused by aortic stiffness is thought to be a contributing factor for several cerebrovascular diseases. The main purpose of this study was to describe the dampening of the pulsatile flow from the proximal to the distal cerebral arteries, the effect of aging and sex, and its correlation to aortic stiffness. Forty-five healthy elderly (mean age 71 years) and 49 healthy young (mean age 25 years) were included. Phase-contrast magnetic resonance imaging was used for measuring blood flow pulsatility index and dampening factor (proximal artery pulsatility index/distal artery pulsatility index) in 21 cerebral and extra-cerebral arteries. Aortic stiffness was measured as aortic pulse wave velocity. Cerebral arterial pulsatility index increased due to aging and this was more pronounced in distal segments of cerebral arteries. There was no difference in pulsatility index between women and men. Dampening of pulsatility index was observed in all cerebral arteries in both age groups but was significantly higher in young subjects than in elderly. Pulse wave velocity was not correlated with cerebral arterial pulsatility index. The increased pulsatile flow in elderly together with reduced dampening supports the pulse wave encephalopathy theory, since it implies that a higher pulsatile flow is reaching distal arterial segments in older subjects.